Evaluation of the Reference Current Generation Methods for Harmonic Compensation Applications using Instantaneous Reactive Power Theory (IRPT) - Lin Xu; Yang Han (Institute of Advanced Engineering and Science, 2013)
This paper presents a critical survey of the reference current generation (RCG) methods for harmonic and reactive power compensation for the electrical distribution systems. A critical review of the p-q method, the d-q(id-iq) method, the p-q-r method, the UPF method and the FBD method are presented for the sake of comparison. In order to mitigate the deficiencies of these existing methods, the modified d-q method, the modified p-q-r method, and the modified p-q method are also presented. The MATLAB simulation of these algorithms is carried out for different grid voltage and load conditions scenarios. It is found that, all these algorithms show similar performance in case of ideal grid voltage scenario. In case of grid voltage unbalance or harmonics, the difference in steady state compensation accuracy among these algorithms is presented. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1675